Who is Responsible? A Situational Brief on the Air Pollution in Lugazi Town - Initiative for Social and Economic Rights (ISER) (Initiative for Social and Economic Rights (ISER), 2013)
For close to two years, residents, workers and passersby in Lugazi Town Council have had to put up with an obnoxious smell that engulfs the town in the late evenings and early mornings. Lugazi town is located in Buikwe District, on the Kampala – Jinja Highway, approximately 50 kilometers east of Kampala. Besides complaints from the residents, the issue of the obnoxious smell has also been reported in the media and there seemed to be a mystery surrounding its source. Although residents and local authority officials blamed the pollution on the Sugar Corporation of Uganda (SCOUL), their management consistently denied this in media reports and employees remained tight-lipped on the subject.